Influences on parents’ fever management: beliefs, experiences and information sources - Anne Walsh; Helen Edwards; Jennifer Fraser (2007)
Aim. To identify parents’ knowledge, beliefs, management and sources of information about fever management. Background. Despite numerous studies exploring parents’ management of childhood fever; negative beliefs about fever and overuse of antipyretics and health services for mild fevers and self‐limiting viral illnesses continue to be reported. Design. Qualitative design using semi‐structured interviews and discussions. Method. Fifteen metropolitan parents whose children were aged six months to five years, volunteered to participate in individual interviews or group discussions. Recruitment was through Playgroup Queensland's online newsletter and letters from two childcare centres to all parents. Verbatim and audio data were collected by an experienced moderator using a semi‐structured interview guide. Data analysis: Two transcripts were independently analysed by two researchers; categories, sub‐headings and codes were independently developed, crosschecked and found comparable. Remaining transcripts were analysed using developed categories and codes. Results. Fever, determined through behavioural changes, was perceived as ‘good’, a warning that something was wrong. High fever, reported as 38·0–39·1 °C, was considered harmful; it must be prevented or reduced irrespective of concerns about antipyretics. Positive febrile experiences reduced concern about fever. Negative experiences such as febrile convulsions, media reports of harm, not receiving a definitive diagnosis, inaccessibility to regular doctors and receiving conflicting information about fever management increased the concerns. Parents seek information about fever from multiple sources such as doctors, books and other parents. Conclusions. Parents’ experiences with and information sources about fever and fever management influenced their knowledge, beliefs and practices. Positive experiences reduce concerns, health service usage and sometimes antipyretic usage. Negative experiences increase concerns, monitoring and antipyretic and health service usage. Relevance to clinical practice. Health professionals need to update their fever management knowledge ensuring that it is based on the latest scientific knowledge. They must provide parents of young children with consistent, reliable information preferably before their first child's first febrile episode.